\( \left(10 x^{2}-9\right)^{\frac{1}{4}}=x \) What is the sum of the solutions to the given equation?
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Bonus Knowledge
To solve the equation \( \left(10 x^{2}-9\right)^{\frac{1}{4}}=x \), we begin by raising both sides to the power of 4 to eliminate the fourth root: \[ 10x^2 - 9 = x^4 \] Rearranging the equation yields: \[ x^4 - 10x^2 + 9 = 0 \] Next, we can make a substitution to simplify this quartic equation. Let \( y = x^2 \). This transforms our equation into a quadratic form: \[ y^2 - 10y + 9 = 0 \] Now, we will factor this quadratic. We look for two numbers that multiply to \( 9 \) and add to \( -10 \). Those numbers are \( -1 \) and \( -9 \). Thus, we can factor it as: \[ (y - 1)(y - 9) = 0 \] Setting each factor to zero gives us the solutions for \( y \): \[ y - 1 = 0 \quad \Rightarrow \quad y = 1 \] \[ y - 9 = 0 \quad \Rightarrow \quad y = 9 \] Recalling that \( y = x^2 \), we substitute back: 1. From \( y = 1 \): \[ x^2 = 1 \quad \Rightarrow \quad x = 1 \quad \text{or} \quad x = -1 \] 2. From \( y = 9 \): \[ x^2 = 9 \quad \Rightarrow \quad x = 3 \quad \text{or} \quad x = -3 \] Thus, the solutions for \( x \) are \( 1, -1, 3, \) and \( -3 \). Next, we find the sum of all these solutions: \[ 1 + (-1) + 3 + (-3) = 0 \] Therefore, the sum of the solutions to the equation is: \[ \boxed{0} \]